Legal Protection for Sharia Capital Market Investors To Increase Investor Confidence Through The ‘Sharia Securities List’ - Wiyanti, Diana; Sumiyati, Yeti; Hendar, Jejen (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
Investors' worldly benefits and blessings in the hereafter are the main considerations in investing in the Islamic Capital Market. Many issuers have registered their companies on the Sharia Securities List based on POJK No. 35/POJK.04/2017 concerning Criteria and Issuance of Sharia Securities List. However, in practice, issuers that have been included in the Sharia Securities List can be removed from the list in the following period because they no longer fulfill the requirements of the POJK. This study aims to analyze the effectiveness of the implementation of investor protection regulations in the Sharia capital market with a focus on issuers' compliance with Sharia principles. The method used is descriptive-analytical with a normative juridical approach, and the analysis is qualitative. The results showed that the regulations related to the Sharia capital market are sufficient. Meanwhile, the implementation of legal protection for investors in the Sharia capital market needs to be improved to further increase investor confidence. This study recommends increased routine supervision by OJK, law enforcement with stricter sanctions for issuers that do not fulfill Sharia principles, and increased transparency of information for investors.